Reduced rate of postpartum readmissions among homeless compared with non-homeless women in New York: a population-based study using serial, cross-sectional data. Issue 4 (16th June 2021) - Sakai-Bizmark, Rie; Kumamaru, Hiraku; Estevez, Dennys; Neman, Sophia; Bedel, Lauren E M; Mena, Laurie A; Marr, Emily H; Ross, Michael G
Abstract : Objective: To assess differences in rates of postpartum hospitalisations among homeless women compared with non-homeless women. Design: Cross-sectional secondary analysis of readmissions and emergency department (ED) utilisation among postpartum women using hierarchical regression models adjusted for age, race/ethnicity, insurance type during delivery, delivery length of stay, maternal comorbidity index score, other pregnancy complications, neonatal complications, caesarean delivery, year fixed effect and a birth hospital random effect. Setting: New York statewide inpatient and emergency department databases (2009–2014). Participants: 82 820 and 1 026 965 postpartum homeless and non-homeless women, respectively. Main outcome measures: Postpartum readmissions (primary outcome) and postpartum ED visits (secondary outcome) within 6 weeks after discharge date from delivery hospitalisation. Results: Homeless women had lower rates of both postpartum readmissions (risk-adjusted rates: 1.4% vs 1.6%; adjusted OR (aOR) 0.87, 95% CI 0.75 to 1.00, p=0.048) and ED visits than non-homeless women (risk-adjusted rates: 8.1% vs 9.5%; aOR 0.83, 95% CI 0.77 to 0.90, p<0.001). A sensitivity analysis stratifying the non-homeless population by income quartile revealed significantly lower hospitalisation rates of homeless women compared with housed women in the lowest income quartile. These results were surprising due to the trend of postpartum hospitalisation rates increasing as income levels decreased. Conclusions: Two factors likely led to lower rates of hospital readmissions among homeless women. First, barriers including lack of transportation, payment or childcare could have impeded access to postpartum inpatient and emergency care. Second, given New York State's extensive safety net, discharge planning such as respite and sober living housing may have provided access to outpatient care and quality of life, preventing adverse health events. Additional research using outpatient data and patient perspectives is needed to recognise how the factors affect postpartum health among homeless women. These findings could aid in lowering readmissions of the housed postpartum population.